Platelet‐to‐lymphocyte ratio predicts the prognosis of patients with non‐small cell lung cancer treated with surgery and postoperative adjuvant chemotherapy. Issue 1 (3rd November 2017) - Toda, Michihito; Tsukioka, Takuma; Izumi, Nobuhiro; Komatsu, Hiroaki; Okada, Satoshi; Hara, Kantaro; Miyamoto, Hikaru; Ito, Ryuichi; Shibata, Toshihiko; Nishiyama, Noritoshi
Abstract : Background: Markers of preoperative tumor immunity, such as platelet‐to‐lymphocyte ratio (PLR), have been reported to be prognostic factors for patients with various cancers. However, the relationship between PLR and the prognosis of non‐small cell lung cancer (NSCLC) patients treated with surgery and adjuvant chemotherapy as a multidisciplinary treatment is unknown. Methods: We enrolled 327 NSCLC patients treated surgically with or without adjuvant chemotherapy (78 and 249 patients, respectively) at our hospital from 2008 to 2012. Patients had no preoperative hematological disease or infection. Preoperative PLR and clinicopathologic characteristics were recorded and their potential associations and prognostic values were assessed by Kaplan–Meier and multivariate Cox regression. The optimal cut‐off value for high and low PLR was calculated from receiver operating characteristic curves. Results: The five‐year overall survival rates for patients with low and high PLR were 78% and 57% ( P < 0.01) for all patients, and 69% and 37% ( P < 0.01) for patients who received adjuvant chemotherapy, respectively. Similarly, the five‐year disease‐free survival rates for patients with low and high PLR were 66% and 62% ( P = 0.03) for all patients, and 47% and 14% ( P < 0.01) for patients who received adjuvant chemotherapy, respectively. Cox proportional hazard regression indicated that high PLR was an independent prognostic factor for both overall and disease‐free survival in the adjuvant chemotherapy group. Conclusion: Elevated PLR predicts poor prognosis in surgically treated NSCLC patients, especially those who receive adjuvant chemotherapy.